Characterization of Post‐Traumatic Osteoarthritis in Rats Following Anterior Cruciate Ligament Rupture by Non‐Invasive Knee Injury (NIKI). Issue 2 (6th October 2019) - Brown, Shannon B.; Hornyak, Jessica A.; Jungels, Ryan R.; Shah, Yash Y.; Yarmola, Elena G.; Allen, Kyle D.; Sharma, Blanka
Abstract : Non‐invasive anterior cruciate ligament (ACL) rupture is an emerging small animal model of post‐traumatic osteoarthritis (PTOA). The non‐invasive nature of this model may make it uniquely suited to study important OA phenomena. Here, PTOA following ACL rupture by a non‐invasive knee injury (NIKI) device was characterized to establish the fundamental pathology and time course of this model in rats. NIKI‐injured knees exhibited changes to the bone, cartilage, synovium, and synovial fluid biomarker profile, hallmark indicators of PTOA‐like pathology. ABSTRACT: Small animal models are essential for studying anterior cruciate ligament (ACL) injury, one of the leading risk factors for post‐traumatic osteoarthritis (PTOA). Non‐surgical models of ACL rupture have recently surged as a new tool to study PTOA, as they circumvent the confounding effects of surgical disruption of the joint. These models primarily have been explored in mice and rabbits, but are relatively understudied in rats. The purpose of this work was to establish a non‐invasive, mechanical overload model of ACL rupture in the rat and to study the disease pathogenesis following the injury. ACL rupture was induced via non‐invasive tibial compression in Lewis rats. Disease state was characterized for 4 months after ACL rupture via histology, computed tomography, and biomarker capture from the synovial fluid. The non‐invasive knee injury (NIKI) model created consistent ACL ruptures without direct damage to other tissues and resulted in conventional OA pathology. NIKI knees exhibited structural changes as early as 4 weeks post‐injury, including regional structural changes to cartilage, chondrocyte and cartilage disorganization, changes to the bone architecture, synovial hyperplasia, and the increased presence of biomarkers of cartilage fragmentation and pro‐inflammatory cytokines. These results suggest that this model can be a valuable tool to study PTOA. By establishing the fundamental pathogenesis of this injury, additional opportunities are created to evaluate unique contributing factors and potential therapeutic interventions for this disease. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:356‐367, 2020